2000
DOI: 10.1098/rsta.2000.0601
|View full text |Cite
|
Sign up to set email alerts
|

The effect of edifice load on magma ascent beneath a volcano

Abstract: A volcanic edi ce exerts a large load at Earth's surface and modi es the stress eld at depth. We investigate how this a¬ects upward dyke propagation towards the surface. For given edi ce dimensions and pressure conditions in the deep magma source, there is a critical density threshold above which magmas cannot reach the surface. This density threshold is a decreasing function of edi ce height. For edi ce heights in the range 0{3000 m, the density threshold spans the density range of common natural magmas (betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 9 publications
5
144
0
Order By: Relevance
“…Initially, the stress gradient due to caldera collapse promotes the rise of magma (Fig.4a). In general, this may lead to post-caldera resurgence (Kennedy et al, 2012) and/or increased volcanism due to the decompression of a shallow reservoir that would favor the rise of magma from a deeper source if the reservoirs are hydraulically connected through a magmatic plumbing system (Pinel and Jaupart, 2000;Hooper et al, 2011). In case of significant unloading (Pl/Pe>5), the vertical orientation of σ3 beneath the caldera promotes shallow, flat-topped magma bodies (Fig.4b).…”
Section: Caldera Collapse Control On the Magma Plumbing Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the stress gradient due to caldera collapse promotes the rise of magma (Fig.4a). In general, this may lead to post-caldera resurgence (Kennedy et al, 2012) and/or increased volcanism due to the decompression of a shallow reservoir that would favor the rise of magma from a deeper source if the reservoirs are hydraulically connected through a magmatic plumbing system (Pinel and Jaupart, 2000;Hooper et al, 2011). In case of significant unloading (Pl/Pe>5), the vertical orientation of σ3 beneath the caldera promotes shallow, flat-topped magma bodies (Fig.4b).…”
Section: Caldera Collapse Control On the Magma Plumbing Systemmentioning
confidence: 99%
“…The lateral growth of sill-like reservoirs is discouraged beyond the ! 11 caldera rim (Fig.4c), where the driving force of magma is reduced (Pinel and Jaupart, 2000).…”
Section: Caldera Collapse Control On the Magma Plumbing Systemmentioning
confidence: 99%
“…It can change the emplacement depth of magmas. Pinel and Jaupart (2000) studied the influence of the gravitational stress on magma ascent and showed that a volcanic edifice can work as a magma filter that prevents the eruption of dense magmas. Their discussion was, however, based on the static criterion for a crack to extend (e.g., Watanabe et al, 1999).…”
Section: Influences Of Topographic Loadmentioning
confidence: 99%
“…Multiple factors combining to generate such composite fields have been advocated and analyzed: loading due to the edifice (e.g., Dahm, 2000;Pinel and Jaupart, 2000;Maccaferri et al, 2011) and unloading (e.g., Maccaferri et al, 2014), the effects of volcano morphology (e.g., Tibaldi et al, 2014;Corbi et al, 2015), the generation of magma reservoirs and calderas (e.g., Tibaldi, 2015) and the anisotropy of host rocks (Gudmundsson, 2011a). Many dykes do not propagate all the way to the surface, but may be arrested by layers with variable associated stress (Gudmundsson and Philipp, 2006).…”
Section: Factors That Could Affect Stress and Strain In The Earsmentioning
confidence: 99%